2021
DOI: 10.3390/antibiotics10010074
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Resistance of Non-O157 Shiga Toxin-Producing Escherichia coli Isolated from Humans and Domestic Animals

Abstract: Non-O157 Shiga toxin-producing Escherichia coli (STEC) is an important pathogen that can cause zoonotic diseases. To investigate the antimicrobial resistance of STEC in China, non-O157 STEC isolates, recovered from domestic animals and humans from 12 provinces, were analyzed using antimicrobial susceptibility testing and whole genome characterization. Out of the 298 isolates tested, 115 strains showed resistance to at least one antimicrobial and 85 strains showed multidrug resistance. The highest resistance ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 50 publications
2
18
2
Order By: Relevance
“…In this study, we found high rates of multidrug resistance (swine: 93.8%; patients: 86.0%). Evidently, in our results, values obtained were higher than those obtained in other studies (Pig -Netherland: 34.2% [4], China: 84.2% [28], Thailand: 84.6% [14]; Humans -Netherland: 7.1% [29], China: 15.2% [28], Thailand: 45.7% [14]) In Korea, antimicrobial use in veterinary (33.2 defined daily doses (DDD) per 1000 inhabitants per day) and human medicine (31.7 DDD per 1000 inhabitants per day) is relatively higher as compared to that in other member countries of the Organization for Economic Co-operation and Development (OECD) (21.3 and 23.7 DDD per 1000 inhabitants per day, respectively) [30,31]. Besides the possible role of increased selective pressure by repeated exposure to therapeutic agents, this is a likely cofactor in the increased frequency of antimicrobial resistance observed among pathogens [32].…”
Section: Discussioncontrasting
confidence: 94%
“…In this study, we found high rates of multidrug resistance (swine: 93.8%; patients: 86.0%). Evidently, in our results, values obtained were higher than those obtained in other studies (Pig -Netherland: 34.2% [4], China: 84.2% [28], Thailand: 84.6% [14]; Humans -Netherland: 7.1% [29], China: 15.2% [28], Thailand: 45.7% [14]) In Korea, antimicrobial use in veterinary (33.2 defined daily doses (DDD) per 1000 inhabitants per day) and human medicine (31.7 DDD per 1000 inhabitants per day) is relatively higher as compared to that in other member countries of the Organization for Economic Co-operation and Development (OECD) (21.3 and 23.7 DDD per 1000 inhabitants per day, respectively) [30,31]. Besides the possible role of increased selective pressure by repeated exposure to therapeutic agents, this is a likely cofactor in the increased frequency of antimicrobial resistance observed among pathogens [32].…”
Section: Discussioncontrasting
confidence: 94%
“…On the other hand, it has the potential to be a reservoir of a mobilized fosfomycin resistance gene. The emergence of fosA7 with a transposase gene downstream on the chromosome of E. coli or fosA7.5 flanked by insertion sequences located on plasmid further supports this hypothesis (Milner et al, 2020;Pan et al, 2021). The fosA7 gene can confer high-level fosfomycin resistance once it is captured by a high copy plasmid or the mobile elements that bring stronger promoters that enhance its expression.…”
Section: Discussionmentioning
confidence: 71%
“…The minimal inhibitory concentrations of all STEC isolates were performed using broth microdilution method as previously described ( Pan et al, 2021 ). The qualitative interpretations of susceptible (S), intermediate (I), resistant (S) strains were determined according to the standard of the Clinical Laboratory Standards Institute guidelines (CLSI 2020).…”
Section: Methodsmentioning
confidence: 99%